2016
DOI: 10.1186/s40902-016-0076-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 4-hexylresorcinol on xenograft degradation in a rat calvarial defect model

Abstract: BackgroundThe objective of this study was to evaluate xenograft degradation velocity when treated with 4-hexylresorcinol (4HR).MethodsThe scapula of a cow was purchased from a local grocery, and discs (diameter 8 mm, thickness 1 mm) were prepared by trephine bur. Discs treated with 4HR were used as the experimental group. Untreated discs were used as the control. X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), antibacterial test, endotoxin test, and scanning electron microscopy (SEM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…The 4-HR compound has anti-microbial activity and is used as an antiseptic [55]. In consideration of these characteristics, in this study, 4-HR was used as a material component in the silk patch in order to prevent bacterial infection and an immune reaction, as this compound is known to inhibit foreign-body reaction and giant cell formation around the graft material area [31]. The 4-HR compound inhibits foreign-body giant cell formation via suppression of the diacylglycerol kinase in macrophages, and induces the biodegradation of the graft material [31,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 4-HR compound has anti-microbial activity and is used as an antiseptic [55]. In consideration of these characteristics, in this study, 4-HR was used as a material component in the silk patch in order to prevent bacterial infection and an immune reaction, as this compound is known to inhibit foreign-body reaction and giant cell formation around the graft material area [31]. The 4-HR compound inhibits foreign-body giant cell formation via suppression of the diacylglycerol kinase in macrophages, and induces the biodegradation of the graft material [31,34].…”
Section: Discussionmentioning
confidence: 99%
“…This compound was used as a food additive to prevent the melanosis of seafood and fruit, and as antiseptics for skin and oral mucosa [29,30]. It was recently employed as a component in silk-based biomaterials because of its antiseptic and anti-inflammatory activities [31]. In addition, in a microvascular anastomosis study, 4-HR was observed to yield anti-thrombotic effects such as blood coagulation delay and the inhibition of thrombus formation [32].…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages had been shown to respond and naturally bound to almost all biomaterials once implanted, including collagen [ 14 ]. It had been demonstrated that macrophages participate in the degradation of biomaterials by the release of a variety of enzymes [ 15 ], mediators of degradation such as reactive oxygen intermediates (ROIs), enzymes, and acid between the cell membrane and biomaterial surface [ 16 ]. Macrophages could fuse and became foreign body giant cells (FBGCs), which were observed at biomaterial-tissue interface of implanted devices and tissue engineering scaffolds [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, 4-HR can inhibit the osteoclast activation, and it may contribute to new bone regeneration. 4-HR has been used as an ingredient of bone graft material, and it has shown favorable results in new bone regeneration [69]. The 4-HR and HA combined graft material has shown higher initial bone regeneration in a rabbit calvarial defect [70].…”
Section: -Hexylresorcinolmentioning
confidence: 99%